Inclusive Institutions for Sustainable Economic Development - Miomir Jakšić; Milica Jakšić (Journal of Central Banking Theory and Practice, 2018)
In recent two decades, due to contributions of political macroeconomics, the focus of macroeconomics turned away from a narrow perspective based on market and privatisation (market fundamentalism) towards a broader perspective based on institutions and values (institutionalism). Within the institutional paradigm, the emphasis nowadays is put on inclusive institutions. The main thesis of one of leading proponents of political macroeconomics, D. Acemoglu, is: "growth is much more likely under inclusive (economic and political) institutions than extractive institutions." Good institutions are characterized by three attributes: 1) they establish and protect property rights; 2) they restrict social elites which strive to expropriate income and property of others members of society; 3) they provide equal chances for employment, social security and civil rights to all individuals. Good institutions contribute to political stability, successful macroeconomic policy, and enhance initiatives. The key role of institutions is to secure stability and continuity. Extractive institutions can negatively affect entrepreneurship and entire economic development in two ways: a) by increasing the opportunity cost, resulting in upward movement of the opportunity cost curve; and b) by affecting return to entrepreneurship resulting in leftward movement of the return to entrepreneurship curve. Apart from independence and accountability of institutions what is needed is sufficient level of inclusion. Inclusion should encompass three dimensions: personal, financial, and political. The introduction of principles of independence, accountability, and inclusion is essential for emergence and performance of all institutions.
Keywords: B10; B15; O13; 330; political macroeconomy; inclusive institutions; sustainability; good governance.